Study of Fall Army Worm (Spodoptera frugiperda) Risk Communication Sources and Information Needs of Rural Maize Farmers in Imo State, Nigeria - J.U., Chikaire; J.O., Ajaero; C.C., Godson–Ibeji; P.A., Onoh; C.O., Osuagwu; J.O., Oparaojiaku; M.N, Ibe; G.O, Aminu (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Army worm infestation has become a thorn on the flesh of maize farmers throughout the century. This is due to a lack of information available to farmers. This paper seeks to unravel the risk communication sources used to alert the farmers and information maize farmers need to combat or adapt to fall armyworm menace. The researchers purposively selected a total of 450 maize farmers randomly from a list of 4500 maize farmers. Questionnaire was used for information sourcing and data analyzed using percentages and mean presented in tabular form. Results showed that the farmers (100%) have knowledge of the fall army worm as they have seen it before; they can identify the larvae and egg (77.7%), know about damage to leaves (100%), have also seen the egg on maize leaves among others. They became aware of armyworm menace through personal observations (95.5%), family and friends (90%), cooperatives (89%), among other sources. The farmers need information on control measures (M=3.04), how to apply chemicals (M=3.50), when to apply chemical (M=3.45), training on chemical application (M=3.35), alternatives crops to cultivate (M=3.01), among others. They face the following challenges in accessing army worm information: communication/language barrier (98%), high level of illiteracy among farmers (96.6%), erratic power supply (100%), inadequate funds/capital (94.4%) and absence of extension staff (98.8%), and many more. It is recommended that use of clear local language on army worm education be encourage, power supply be improved, data charges reduced, communication facilities be improved and extension service delivery strengthened.